Where Neuroscience and Art Embrace; The Neuroaesthetics - Mohammad Torabi Nami; Hasan Ashayeri (Basic and Clinical Neuroscience, 2011)
Neuroscience has recently contributed a lot to the understanding of aesthetic experience features. Science, art and creativity are not really distinctively different entities. The parallelism seen between the properties of art and organizational principals of the brain has been highlighted through neuroaesthetic studies. Aesthetic as a subjective experience has comprehensively been studies through neuro-scientific, psychological, sociologic and cultural standpoints. This is a controversial topic in cognitive neuroscience, meanwhile seemingly varied results of the conducted researches in this field may be conceptualized in a framework linking aesthetics to neuroscience of affective visual processing, reward circuitries and the nature of decision making. Approaching the question of art-brain parallelism, is along side with elucidating the relation between perception and aesthetic experience,and the features of aesthetic judgment and reward. Moreover, other factors such as cultural underpinnings undoubtedly come into play. In this review we used expert opinions and literary notions to present a report on how neuroscience has so far elaborated on different features of the aesthetic phenomenon hoping to probe areas of neuroaeshetic research which can potentially assess our cultural interface with the aesthetics and cognitive neuroscience.